Earth System Governance:: Facing the Challenges of Climate Change - Vieira, Susana Camargo (Sustainability in Debate, 2013)
YOUNG, Oran R. Institutional Dynamics: Emergent Patterns in International Environmental Governance. Cambridge (Massachusets, USA): The MIT Press, 2010. Earth System Governance Series. 225p. (Paperback; alkaline paper). ISBN 978-0-262-51440-8.